Orthogonal Optimization Design of Driving Sprocket Parameter of Scraper Conveyor - Su huayang; Wang Shuping; Yang Zhaojian; Zhang Yaocheng (Jixie chuandong)
The wear of ring sprocket is the main factor affecting the service life of ring chain. In order to analyze the key parameters affecting the wear of ring sprocket, by using the SolidWorks， the model of driving sprocket and ring chain of scraper conveyor is built, and the multi-factor and multi-level orthogonal experiments are designed. The stress state when the sprocket with different parameters contaccts with the ring china is analyzed by ANSYS Workbench module. According to the experimental results, the influence of sprocket parameters on the contact stress of driving sprocket and ring link is analyzed, and the optimum combination of parameters in several tests is determined. The analysis and verification results prove the validity of the research conclusions.